Pengaruh Program Customer Relationship Management (Continuity Marketing, One To One Marketing, Dan Partnering Program) Terhadap Loyalitas Pelanggan Pada Toko Online Lazada Di Kota Mataram - Waidatul Ilmi; Hendri Setiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study examines the effect of the Customer Relationship Management (Continuity Marketing, One to One Marketing, and Partnering Program) programs on the Customer Loyalty of Lazada online store in the city of Mataram. This research was conducted on 75 respondents namely Lazada customers in Mataram City aged 18-45 years who have shopping experience at Lazada at least 2 times. This research is an associative quantitative study carried out by filling out a questionnaire and then analyzed using an independent sample t-test. The results of this study indicate that One to one marketing has a positive and significant effect on customer loyalty of Lazada online stores. While Continuity Marketing and Partnering Program have a negative but not significant effect on the loyalty of Lazada online store customers in the city of Mataram. Keywords: Continuity Marketing, One to One Marketing, Partnering Program, Customer Loyalty